The state of entrepreneurship education in Portugal: an empirical study on a nascent system in the European Union policy framework - Redford, Dana Thacher (2011)
Portugal has a nascent entrepreneurship education system at the post-secondary level that aims to address several areas within the European Union policy context. This research finds that Portugal is more than 20 years behind the United States in the development of educational offerings in this area. During the academic year 2005/2006 only 826, or 0.2%, of students at the post-secondary level in Portugal participated in an entrepreneurship class. Currently only 14.8% of students believe that the Portuguese educational system develops a state of mind that encourages the creation of new firms. In developing policy in this area findings highlight regional differences, gender considerations as well as the prominence of the “public sector” mindset or predisposition of post-secondary students relating to their first job experience are important factors to consider. The few courses in Portugal that do exist focus too heavily on teaching business plan development and are almost exclusively located in the area of management. The reliance on lecture formats instead of experiential learning techniques needs to evolve if this area is to move from being teacher-centered to learner-centered. Of the universities that offer courses, 33% also have centers for entrepreneurship and several more (23.8%) plan to develop one on their campus. Portuguese professors believe that entrepreneurship education will positively evolve in quality and quantity in the future. This is good news, as it was found that 63.7% of post-secondary students believed in the possibility of owning their own business in the future.